WAJAH PENDIDIKAN MULTIKULTURAL SEKOLAH DASAR INDONESIA : SEBUAH TINJAUAN LITERATUR SISTEMATIS - Istianingrum, Risqi; Hidayat, Muhamad Taufik (JURNAL TARBIYAH, 2023)
The implementation of multicultural education can be a solution of conflict and disharmony in the society. This study aimed to analyzed models, results and constraints of multicultural education in elementary schools in Indonesia. The method used was Systematic Literature Review (SLR). The techniques used in this study were documenting and revising articles. The process of analyzed the quality of data by means of extraction, analyzed and carried out synthesis. The assessment technique for assessing the validity of the data was check and recheck. The results of this study indicated that the multicultural education in elementary schools has various ways for conveying material such as pop up book media containing diversity and writing poetry based on multiculturalism. Multicultural education can form students to be a tolerant person among Indonesian who have various cultures. The constraints experienced by students such as facilities. This study has three suggestions. First, elementary school teachers must be able to choosing appropriate multicultural material for learning. Second, there is a need for elementary school teachers in the process of integrating multicultural elements into learning activities. Third, the need for government support for curricula related to effective multicultural education. This study described the learning model, results and constraints of multicultural education in elementary schools of Indonesia.